Adsorption of Methylene Blue on the Composite Sorbent Based on Bentonite-Like Clay and Hydroxyapatite - Alexandr Ivanovich Vezentsev; Dang Minh Thuy; Lidia Fedotovna Goldovskaya-Peristaya; Nadezhda Alexandrovna Glukhareva (Universitas Gadjah Mada, 2018)
The adsorption of methylene blue from model aqueous solutions on bentonite-like clay, hydroxyapatite, and a composite sorbent has been investigated. The kinetic and thermodynamic parameters of adsorption in the temperature range 298–333 К have been calculated. The process is found to obey Langmuir isotherm equation. It is spontaneous but slightly endothermic. The maximal sorption capacity of the composite sorbent toward methylene blue is 175.4 mg/g at 25 °С that is 1.3 times more than that for bentonite-like clay and 17.8 times more than that for hydroxyapatite. Kinetics of the process is due to the combination of external and internal diffusion and can be described better by the model of pseudo-second order reaction.